Engineering applications of FPGAs : chaotic systems, artificial neural networks, random number generators, and secure communication systems /: chaotic systems, artificial neural networks, random number generators, and secure communication systems. ([2016]) - Tlelo-Cuautle, Esteban; Rangel M., José de Jesús; Fraga, Luis Gerardo de la
No abstract available